2017
DOI: 10.3324/haematol.2016.163337
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles of bone marrow stromal cells rescue chronic lymphocytic leukemia B cells from apoptosis, enhance their migration and induce gene expression modifications

Abstract: Interactions between chronic lymphocytic leukemia (CLL) B cells and the bone marrow (BM) microenvironment play a major function in the physiopathology of CLL. Extracellular vesicles (EVs), which are composed of exosomes and microparticles, play an important role in cell communication. However, little is known about their role in CLL / microenvironment interactions. In the present study, EVs purified by ultracentrifugation from BM mesenchymal stromal cell (BM-MSC) cultures were added to CLL B cells. After their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 43 publications
1
74
0
Order By: Relevance
“…Furthermore, both direct cell-cell contact through nurse cells 212 and even extracellular vesicles affect the differentiation direction of the MSC. 213 Those vesicles are abundantly present around SaOS-2 and HUVEC cells. 214 In addition, it has been shown that the topology of the surrounding matrices controls the gene expression systems within MSCs and in turn also the phenotype of the differentiated cells.…”
Section: Cell-laden 3d Bio-printed Implantsmentioning
confidence: 97%
“…Furthermore, both direct cell-cell contact through nurse cells 212 and even extracellular vesicles affect the differentiation direction of the MSC. 213 Those vesicles are abundantly present around SaOS-2 and HUVEC cells. 214 In addition, it has been shown that the topology of the surrounding matrices controls the gene expression systems within MSCs and in turn also the phenotype of the differentiated cells.…”
Section: Cell-laden 3d Bio-printed Implantsmentioning
confidence: 97%
“…Bone marrow mesenchymal stem cell‐derived exosomes are reported to act as communicators during drug treatment. Transcriptomic profiles further demonstrated that the underlying mechanism was through the enhancement of cell migration and induction of relevant gene expression, such as Ccl3/4 , Ccl4 and Cxcr4 59 . In addition, it was found that exosomes were able to promote breast cancer cell metastasis through the transfer of miRNA‐23b and to suppress target Marcks mRNA expression 60 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that miR-221-3p was highly expressed in BMMSC-derived MVs. Besides, it has been reported that bone marrow stromal cell-derived MVs can attenuate the B cell apoptosis in chronic lymphocytic leukemia, also promote cell migration and induce gene expression and modification (Crompot et al, 2017). Hence, this study focused attention on the BMMSC MVs-derived miR-221-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that tumor-derived MVs (TMV) can interact directly with tumor cells and play a macro-messenger role to promote the transfer of molecular substances between tumor cells to facilitate tumor growth (Stec et al, 2015a,b). MVs derived from bone marrow mesenchymal stem cell (BMMSC) can promote tumorigenesis and development (Crompot et al, 2017;Boyiadzis and Whiteside, 2018). miRNAs in MVs, as post-transcriptional regulatory elements, directly regulate gene expression, target mRNA expression and translation or induce mRNA degradation to reduce protein synthesis by directly binding with the 3 ′ -untranslation region (3 ′ -UTR) of specific mRNA targets (Braicu et al, 2015;Jerez et al, 2019), ultimately induce multiple pathophysiological processes, such as leukemia stem cell formation, regulation of tumor cell proliferation, angiogenesis, invasion, metastasis, and immune escape to modulate leukemia development (Braicu et al, 2015;Del Principe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%